A3 SYMPOSIUM BERGERAC VISCOSITÉ TYPE F (DP) Manuco.pdf - Gill, Philip (Cranfield University, 2023)
SEC (Size Exclusion Chromatography) correlation viscosity= f (DP) Claude GUILLAUME MANUCO
Keywords: 'nitrocellulose'